2016
DOI: 10.18632/oncotarget.7897
|View full text |Cite|
|
Sign up to set email alerts
|

Protective role of p53 in skin cancer: Carcinogenesis studies in mice lacking epidermal p53

Abstract: p53 is a protein that causes cell cycle arrest, apoptosis or senescence, being crucial in the process of tumor suppression in several cell types. Different in vitro and animal models have been designed for the study of p53 role in skin cancer. These models have revealed opposing results, as in some experimental settings it appears that p53 protects against skin cancer, but in others, the opposite conclusion emerges. We have generated cohorts of mice with efficient p53 deletion restricted to stratified epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…showed that p53 deficiency in mouse embryonic stem cells leads to deregulated DNA methylation patterns, increases phenotypical heterogeneity of these cells and interferes with their differentiation [ 106 ]. Early functional loss of epidermal p53 may also account for the histological diversity of the tumor types in our system, as recently shown in a knock-out mouse model [ 107 ]. Therefore, loss of functional p53 in a nKSCC harboring p53 mutant R266C ( Fig 11 ) may favor dedifferentiation [ 64 ] which could explain the differences in viral load between KSCCs and nKSCCs.…”
Section: Discussionmentioning
confidence: 60%
“…showed that p53 deficiency in mouse embryonic stem cells leads to deregulated DNA methylation patterns, increases phenotypical heterogeneity of these cells and interferes with their differentiation [ 106 ]. Early functional loss of epidermal p53 may also account for the histological diversity of the tumor types in our system, as recently shown in a knock-out mouse model [ 107 ]. Therefore, loss of functional p53 in a nKSCC harboring p53 mutant R266C ( Fig 11 ) may favor dedifferentiation [ 64 ] which could explain the differences in viral load between KSCCs and nKSCCs.…”
Section: Discussionmentioning
confidence: 60%
“…The genotyping of K5-IKKβ, p53 EKO /K5-IKKβ and Ink4a/Arf KO /K5-IKKβ mice was performed by PCR analysis of tail DNA as previously described. [35][36][37][38] K5-IKKβ mice are available from the European Mouse Mutant Archive (code EM:09179). The expected genotypes were obtained in roughly Mendelian rates in the different crosses.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse experimental procedures were performed according to European and Spanish regulations and were approved by the Ethics Committee for Animal Welfare of CIEMAT and by the legal authority (protocol codes BME02/10 and PROEX086/15). Transgenic mice used in this work have been described previously: line L1of K5-IKKb mice in B6D2 hybrid background (20); TgAC (FVB/ NTac-Tg(Hba-x-v-Ha-ras)TG.ACLed) mice (21), p53 EKO mice (22,23), and Ink4a/Arf KO mice (lacking p16 and p19 proteins in FVB background; ref. 24).…”
Section: Mice and Treatmentsmentioning
confidence: 99%
“…Genotyping of K5-IKKb and of p53 and Ink4a/Arf loci were performed by PCR analysis of tail DNA, as described previously (20,23,25).…”
Section: Genotyping Of Micementioning
confidence: 99%
See 1 more Smart Citation